Simulation of LNAPL migration and remedition at a petroleum refinery site - Nadzif, Nor Farina (2015)
This study presents the results of simulation for the migration of light nonaqueous phase liquid (LNAPL) contamination at Port Dickson petroleum refinery and a remediation by steam injection using T2VOC numerical model. A kerosene leak of 20 years period from the distributing pipelines has caused a serious LNAPL contamination in the subsurface environments. Site investigations were conducted to identify the source of leak and to delineate the contaminations plumes. The concern raised was whether the LNAPL has travelled offsite and has reached the subsurface environments of the down-gradient residential areas. The support tools considered in this study for delineation and remedial solution are based on theexisting site investigations and the application of the numerical model. Numerical simulation will investigate the distribution of LNAPL and remediation within economical and shorter timeline, in response to management decision. In this study, T2VOC is used to simulate a ‘three-phase non-isothermal single component flow’ in a partially saturated homogeneous media for the injection of 876.5 kg of o-xylene (component of kerosene) in a two-dimensionalmodel. The model generated a distribution of LNAPLat a distance of 10 m for 5 years of injection period, while site investigation showed a migration plume of 100 m for 20 years of leak period. Verification with the formulation computed a plume length of 19.9 m. The numerical simulation results are underestimated compared to the site investigation data, although the distribution showed the same behavior for both of methods with time.Based on the results of the numerical simulation and validation with site investigation data, the LNAPL distribution in the subsurface of the refinery was unlikely to migrate offsite to the residential area. While, the simulation of remediation with steam injection showed that 90% of the LNAPL saturation was removed in 20 days of treatment. The result has therefore demonstrated the effectiveness of steam injection process for this study.